Pediatric Epilepsy Surgery - Akalan, Nejat; Di Rocco, Concezio; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2012)
The contributions in this volume cover recent advances and changing concepts on diagnosis and treatment of resistant epilepsy in children. Topics treated are new insights on mechanisms of epileptogenesis in developing brain, multimodality imaging in pediatric intractable epilepsy, pediatric intractable epilepsy syndromes, pediatric temporal lobe epilepsy surgery, critical review of palliative surgical techniques for intractable epilepsy, treatment modalities for intractable epilepsy in hypothalamic hamartomas, contemporary management of epilepsy in tuberous sclerosis.
Keywords: Medicine; Neurosurgery; Medicine & Public Health; Neurosurgery; Electronic books